Determinants Of Financial Performance In Local Governments In District/City In Indonesia - Irna Triannur Lubis; Etty Harya Ningsi (Institute of Computer Science (IOCS), 2022)
This study aims to determine and analyze the effect of government size, balancing funds, and economic growth on regional financial performance in districts/cities in Indonesia. This type of research is causal and the object of this research is all districts and cities in Indonesia. The data used is secondary data obtained from the Directorate General of Fiscal Balance and the Central Statistics Agency for the period 2014-2018 with a total sample of 2,056 research data. Using a quantitative approach and data analysis using a simple regression analysis model. The results showed that Government Size had a positive effect, Balanced Funds had a negative effect, and Economic Growth had a negative effect on Regional Financial Performance.